Penerapan Sekolah Bahtsul Masail untuk Meningkatkan Kompetensi Kader Aktivis Fiqih Melalui Lembaga Bahtsul Masail PWNU Jawa Barat - Ilmin Nafi; Zakaria (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
This study aims to describe the application of Bahtsul Masail School in improving the competence of fiqh activist cadres through Bahtsul Masail PWNU Institution in West Java. The research method used is descriptive qualitative with Case Study approach. Data were obtained through observation, interviews, and documentation involving ten informants, consisting of administrators, resource persons, and activists. The results showed that the Bahtsul Masail school program plays an important role in forming a strong and competent cadres in understanding and solving Fiqh problems in the community. In addition to equipping participants with Fiqh, this program also teaches public communication techniques and character strengthening. The main supporting factors include full support from PWNU West Java and the enthusiasm of participants in learning. The inhibiting factors include time constraints and classic book reference sources. The conclusion of this study confirms that Bahtsul Masail School is a strategic innovation in the cadre of religious activists who are knowledgeable and ready to face the social dynamics of religion in the modern era.